Effects of Disclosing Influencer Marketing in Videos: An Eye Tracking Study among Children in Early Adolescence. Issue 1 (February 2020) - Van Reijmersdal, Eva A.; Rozendaal, Esther; Hudders, Liselot; Vanwesenbeeck, Ini; Cauberghe, Veroline; Van Berlo, Zeph M.C.
This study focused on the effects of sponsorship disclosure timing on children's ability to understand that social influencer videos are sponsored. The study also investigated how sponsorship disclosure timing affects children's attitudes toward the sponsoring brand, the video, and the influencer. An experiment among 272 children in early adolescence (10–13 years of age) was conducted using eye tracking. Results show that a disclosure shown prior to the start of the videos leads to more visual attention than a disclosure shown concurrently with the start of videos. Consequently, disclosure prior to the start of videos is better processed, as indicated by disclosure memory, which then leads to a better understanding that the content is sponsored. This understanding evokes a more critical attitude toward the sponsored content in the video, and results in less positive attitudes toward the brands, the videos, and the influencers. Theoretically, this study provides insights into the mechanisms that explain disclosure timing effects among children in early adolescence. Practically, this study offers recommendations to policy makers to develop sponsorship disclosures that can increase transparency of online embedded advertising to minors.